Pengaruh Variasi Diameter Disc Dan Jumlah Lubang Pada Piringan Cakram Terhadap Jarak Pengereman dan Temperatur Pada Piringan Cakram - Moch. Alifal Fain Zulfa Akbar; Purwoko Purwoko; Khambali Khambali; Ahmad Hanif Firdaus (International Forum of Researchers and Lecturers, 2025)
Disc discs are the main component in a motorcycle braking system that functions to convert kinetic energy into heat energy through friction. The geometric design of the disc, including the diameter and number of holes, affects the effectiveness of braking as well as the heat dissipation ability. This study aims to analyze the effect of variations in diameter and number of holes on disc discs on braking distance and disc temperature. The research method used was an experimental method with three variations in disc diameter (190 mm, 220 mm, and 260 mm) and three variations in the number of holes (30, 36, and 42 holes). The test was carried out through a controlled braking procedure at an initial speed of 40 km/h on flat road surfaces with stable weather conditions. Braking distance data is measured using ultrasonic sensors, while disc temperature is recorded with a high-accuracy infrared thermometer. The results showed that the diameter of the disc disc had the most significant influence on the braking distance. The larger the diameter, the greater the braking moment resulting so that the stopping distance becomes shorter. The number of holes in the disc also plays a role in heat dissipation because the holes enlarge the heat dissipation area. However, the increase in the number of holes tends to slightly increase the braking distance due to a reduction in the area of frictional contact field. The most optimal configuration is found on a 260 mm diameter disc with 42 holes, which results in the shortest braking distance of 8.25 meters and the lowest temperature rise of 4.47°C. Statistical analysis using Two-Way ANOVA confirmed that the diameter and number of holes had a significant effect individually, but there was no significant interaction between the two. These findings confirm that the selection of the right disc dimensions is critical to improving braking performance, thermal efficiency, and rider safety.